2019
DOI: 10.1002/lary.28146
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of clinical scoring tools for the diagnosis of pediatric obstructive sleep apnea

Abstract: Objectives To assess the diagnostic test accuracy of questionnaire and clinical examination‐based scoring tools in the diagnosis of pediatric obstructive sleep apnea (OSA). Methods A comprehensive literature search was performed to identify studies published from 1960 to 2018 that evaluated the accuracy of clinical scoring tools in the diagnosis of pediatric OSA. Studies that did not include attended polysomnography as a reference standard were excluded. The study populations were children under 18 years old w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 53 publications
2
41
0
1
Order By: Relevance
“…These results are consistent with a recent systematic review which investigated the diagnostic accuracy of clinical scoring tools for pediatric OSA. 22 We also found that children with larger tonsils were more likely to have OSA by PSG ( P = .0007). There is conflicting data on these associations in the literature with some studies finding history 13,14 and tonsil size 15,19 to be poor predictors of OSA severity whereas others report the contrary.…”
Section: Discussionsupporting
confidence: 53%
“…These results are consistent with a recent systematic review which investigated the diagnostic accuracy of clinical scoring tools for pediatric OSA. 22 We also found that children with larger tonsils were more likely to have OSA by PSG ( P = .0007). There is conflicting data on these associations in the literature with some studies finding history 13,14 and tonsil size 15,19 to be poor predictors of OSA severity whereas others report the contrary.…”
Section: Discussionsupporting
confidence: 53%
“…It was identified that the OSA-18 was initially designed as a diseasespecific quality of life tool that does not predict obstructive sleep apnea (OSA) symptoms consistent with the gold-standard PSG. Recently Patel et al (151) scrutinized the accuracy of such clinical scoring tools. Additionally, the study by Soh et al (80) acknowledged that there exists a lack of parental understanding of some items and their wording in the original instrument.…”
Section: Discussionmentioning
confidence: 99%
“…14 In an effort to identify pediatric patients who are at risk of OSA, multiple studies have emerged, and have focused on the development of a questionnaire tool. [15][16][17][18] However, the majority of these questionnaires is generally too lengthy and time-consuming to be used as a screening tool by primary care physicians in their customary busy practices, since each of such questionnaires includes between 22 and 40 questions. 2,19 In addition, most of these questionnaires do not accurately predict a diagnosis of pediatric OSA as collaborated by a PSG.…”
Section: Introductionmentioning
confidence: 99%
“…2,19 In addition, most of these questionnaires do not accurately predict a diagnosis of pediatric OSA as collaborated by a PSG. 17 As a potential solution, Spruyt and Gozal conducted a comprehensive machine learning analysis of a large number of a priori relevant questions related to pediatric OSA symptoms, and a set of six short, hierarchically arranged questions was proposed as a new screening instrument, the Pediatric Obstructive Sleep Apnea Screening Tool (POSAST). The POSAST was brief and easy to use in clinical practice, 20 and was subsequently validated in the English language, 18 whereby using an equation-derived score ≥ 1 yielded a sensitivity of 83%, a specificity of 64%, positive predictive value (PPV) of 28%, and negative predictive value (NPV) of 96% for diagnosing moderate and severe OSA (apnea-hypopnea index, AHI ≥ 5 events/h).…”
Section: Introductionmentioning
confidence: 99%